Students’ difficulties in learning English speaking: A case study in a Muslim high school in the South of Thailand - Bushro Apichat; Nur Fatimah (Universitas Ahmad Dahlan, 2022)
The demand on using English as a means of communication is still a challenge for learners of English as a foreign language. The objectives of this study are finding out students’ difficulties in learning English speaking and the factors causing students' difficulties in learning English speaking. This study is descriptive qualitative. The data were obtained through interview. The research involved 10 students of the second semester of high school in a muslim school, in the South of Thailand. The results of the research showed that the students had difficulties in learning English speaking. In addition, they also have difficulty in pronunciation. Some sounds are difficult for students to produce. This was caused by internal and external factors. The internal factors include motivation, vocabulary, grammar, pronunciation, fluency, shyness and also lack of self-confidence. It made students difficult to speak English. The external factors include the environment, teacher, the facility and the students’ lack of the opportunity to use English.